Exploring medical student well-being during transition: a realist inquiry - Melvin, Anna (2022)
Background Issues relating to well-being are widely discussed in medical education and the wider profession, however, well-being is poorly conceptualised and theorised, limiting our understanding of the issues. Transitions have been highlighted as a particular area of concern for well-being. The transition literature has tended to focus on learners’ struggles, emphasising learner skill and knowledge deficits as the source of their difficulties and poorer well-being. This has resulted in limited understanding of the wider environmental factors and underlying causes of learners’ well-being through transition experiences. In this work, transition was conceptualised more broadly as an ongoing developmental process influenced by both environmental and individual factors, with the experiences in one transition affecting the next. This research aimed to improve the knowledge of how well-being is affected during transition by taking a theory-building approach, firstly clarifying the concept of well-being, and then exploring how both student and environmental factors affect well-being through underlying psychological processes during transition, and the links between well-being and learning.